Armed Robbery at Sea di Selat Malaka: Keterbatasan Yurisdiksi Universal dan Kebutuhan Kerja Sama Regional dalam Hukum Laut Internasional - Andi Tenri Oddang (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The increase in shipping intensity in the Straits of Malacca and Singapore/SOMS is directly proportional to the increasing threat of armed robbery at sea which reached 108 incidents in 2025, the highest in the period 2007-2025. This study analyzes the distinction of piracy and armed robbery at sea in international maritime law and the limitations of the application of universal jurisdiction based on UNCLOS 1982. Using the normative juridical method, the results show that the UNCLOS regime, IMO Resolution A.1025(26) which is soft law and the 1988 SUA Convention are not adequate to deal with this crime, because most of them are opportunistic and fall within the jurisdiction of coastal states. Therefore, it is necessary to strengthen regional cooperation which includes the accession of ReCAAP by the three coastal states and the strengthening of coordinated hot pursuit mechanisms, joint patrols and the integration of real-time information sharing trilaterally between coastal states as a concrete implementation of the principle of aut dedere aut judicare.